Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja Terhadap Kinerja Guru SMP Negeri di Kabupaten Minahasa Tenggara - Hosang, Yudita Elvira; Handoko, Yunus; K, Tin Agustina (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Teacher performance is very important for achieving educational goals. This research was conducted with the aim of assessing the influence or impact of leadership, motivation, and work discipline on the performance of state junior high school teachers in Southeast Minahasa Regency. The quantitative method was used by taking a sample of 80 public junior high school teachers from a total population of 398 teachers. Multiple linear regression analysis was performed using SPSS 25. The results showed that leadership had no effect on teacher performance. Meanwhile, work motivation and discipline have a significant positive effect on teacher performance. This finding confirms the importance of increasing the motivation and work discipline of teachers to improve their performance in the research area.